Comparison of the Effectiveness of Subcutaneous Insulin Injection between Upper Arm and Abdominal Sites in Type II Diabetes Mellitus Patients with Normal and Above Normal Body Mass Index - Khairina, Ana; Ihsan, Mohammad Robikhul; Susanti, Vina Yanti (Acta Interna The Journal of Internal Medicine, 2021)
Background. Type II Diabetes Mellitus (DM) has high morbidity and mortality. One of DM therapy is insulin. Insulin effectiveness is affected by the injection site and the thickness of the fat in the injection site. Several studies on the effectiveness of insulin injection sites have been conducted, but the results still vary.Objective. To determine the difference in the effectiveness of subcutaneous insulin injections between the upper arm and abdominal sites on changes in capillary glucose levels in type II diabetes mellitus patients with normal and above-normal body mass index (BMI).Methods. The research design used a quasi-experimental repeated measure design. The research subjects were patients diagnosed with type II DM, age ≥ 40 years, hospitalized in the ward of Dr. Sardjito Hospital Yogyakarta. The effectiveness of insulin injection is described by the difference between 2-hours postprandial glucose (2hPPG) minus fasting blood glucose (FBG) (Δ2hPPG-FBG). Δ2hPPG-FBG was taken on the site of the upper arm and abdomen. Patients were classified based on normal and above normal BMI. Statistical analysis was performed using paired T-tests.Result. There were 14 patients with normal BMI and 11 patients with above normal BMI. Paired T-test showed a significant difference in Δ2hPPG-FBG between the upper arm and abdominal sites in normal BMI patients (p=0.028) with a mean of Δ2hPPG-FBG for the upper arm site of 26,14±38.18 mg/dL, and a mean of Δ2hPPG-FBG of the abdominal site -0.64±50,62 mg/dL. Paired T-test showed no significant difference in Δ2hPPG-FBG between the upper arm and abdominal sites in patients with an above-normal BMI (p = 0.239).Conclusion. The effectiveness of subcutaneous insulin injection in the abdominal site was better than in the upper arm site in patients with normal BMI. There was no difference in the effectiveness of subcutaneous insulin injection between the upper arm and abdominal sites in patients with an above-normal BMI.